The potential of patient-based nurse staffing – a queuing theory application in the neonatal intensive care setting - Sandra Sülz; Andreas Fügener; Michael Becker-Peth; Bernhard Roth (Health Care Management Science, 2024)
Abstract Faced by a severe shortage of nurses and increasing demand for care, hospitals need to optimally determine their staffing levels. Ideally, nurses should be staffed to those shifts where they generate the highest positive value for the quality of healthcare. This paper develops an approach that identifies the incremental benefit of staffing an additional nurse depending on the patient mix. Based on the reasoning that timely fulfillment of care demand is essential for the healthcare process and its quality in the critical care setting, we propose to measure the incremental benefit of staffing an additional nurse through reductions in time until care arrives (TUCA). We determine TUCA by relying on queuing theory and parametrize the model with real data collected through an observational study. The study indicates that using the TUCA concept and applying queuing theory at the care event level has the potential to improve quality of care for a given nurse capacity by efficiently trading situations of high versus low workload.
Keywords: 330; Nursing demand; Flexibility; Quality; Queuing; Staffing; Operations research; Operations management